Philosophical aspects of the theory of cultural modernization (Journal of Philosophy Culture and Political Science, 2018)
This article considers cultural modernization as one of the functions of the modernization process. Cultural modernization is both global and national. The article presents a socio-philosophical analysis of cultural modernization and its cultural, ideological and aesthetic aspects. The inadmissibility of Western cultural modernization as a universal regularity is shown. In the world cultural matrix, different cultural paradigms develop on their own cultural basis. At the present stage, the constant development of the cultural modernization program has shown the need to develop new models. In the article, the authors emphasized the complexity of modernization and the importance of its study in a multifaceted aspect. In the middle of the twentieth century, there were many theories of worldwide modernization. Among them: classical theory, theory of postmodernization, ecological theory of modernization, reflexive theory of modernization, theory of plurality of modernization, secondary theory of modernization, etc. In the article the authors give a philosophical review of six theories of modernization.Key words: culture, modernization, modernization of culture, philosophy of culture, aesthetics.